1982
DOI: 10.1055/s-0038-1657146
|View full text |Cite
|
Sign up to set email alerts
|

Partial Characterization of a Fibrinolytic Inhibitor Produced by Cultured Endothelial Cells Derived from Human Umbilical Vein

Abstract: SummaryA preliminary characterization of a fibrinolytic inhibitor released by human umbilical vein endothelial cells in primary culture is reported. This molecule of Mr comprised between 2 × 105 and 106 and of μ2 mobility precipitates at 43% ammonium sulphate saturation and is totally adsorbed on Concanavalin A Sepharose 4 B. A possible relationship with a macroglobulins is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…This may be especially true of cultured endothelial cells because all endothelial cells tested, including those isolated from humans (8)(9)(10)(11)36), rabbits (6,7), and now cows have been shown to contain both activities. Obviously, then, special consideration should be given in designing any experimental approach to characterize and quantitate the fibrinolytic components of such cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be especially true of cultured endothelial cells because all endothelial cells tested, including those isolated from humans (8)(9)(10)(11)36), rabbits (6,7), and now cows have been shown to contain both activities. Obviously, then, special consideration should be given in designing any experimental approach to characterize and quantitate the fibrinolytic components of such cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cultured rabbit (6,7) and human (8)(9)(10)(11) endothelial cells were found to be associated with an antifibrinolytic activity, suggesting that endothelium itself also may produce molecules that modulate the fibrinolytic activity of the vessel wall. However, no such inhibitor activity has been detected in confluent bovine aortic endothelial cells (BAEs) (9,12).…”
mentioning
confidence: 99%
“…When lesser quantities of UK (10 rulml, -2 nM) were added, the major inhibitor of UK was reported to be a2-antiplasmin (22). The concentration of free PA-inhibitor in the plasma of healthy persons is in general below 5 U per ml (0,15 nM) (7,8,11).Thus the addition of UK in a large molar excess compared to that of free PA-inhibitor explains why these studies did not identify the primary inhibitor of UK in human plasma Fast-acting inhibitors of UK have been found in extracts of human placenta (24,25) , and in the conditioned media of fibroblasts (26,27), endothelial cells (28,29), hepatoma cells (30), monocytes and macrophages (31)(32)(33). At present the relationship of these inhibitors with the plasma PA-inhibitor is not yet established.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we examine the effects of lipopolysaccharide (LPS) on the production of fibrinolytic inhibitor by cultured human endothelial cells. The ability of these cells to synthesize inhibitor(s) of plasminogen activators has been demonstrated previously (7,10,12,22,28). Recently, we have observed that muramyl dipeptide (MDP), the immunoadjuvant properties of which have been well documented (3,20), could stimulate this fibrinolytic inhibitor synthesis (6).…”
mentioning
confidence: 82%